A reliability framework for safe octorotor UAV flight operations - Thanaraj, T. (2023)
Airworthiness of multirotor unmanned aerial vehicles is of utmost importance for ensuring safe flight operations, especially in high-risk airspace. The propulsion system plays a critical role in determining the UAVs' stability and control, and their failures can render UAVs into significant hazards. Assessing the reliability of the propulsion system provides valuable insight into the overall airworthiness of the UAVs, benefitting both regulators and operators. Hence, this paper proposes a framework that integrates controllability analysis with Markov chain modeling to evaluate UAV reliability. The controllability analysis determines combinations of propulsion unit failures in which the UAV remains controllable, which are then modeled as Markov states. This framework is applied to a class of octorotor UAVs, comparing their reliability with other multi-rotor UAVs and examining the influence of different payloads. The results demonstrate the superior reliability of octorotor UAVs, emphasizing their increased suitability for high-risk airspace flight operations compared to other multirotor UAVs.